Interpretable Machine Learning for High-Accuracy Reservoir Temperature Prediction in Geothermal Energy Systems - Mohammadali Ahmadi (Energies)
Accurate prediction of reservoir temperature is critical for optimizing geothermal energy systems, yet the complexity of geothermal data poses significant challenges for traditional modeling approaches. This study conducts a comprehensive comparative analysis of advanced machine learning models, including support vector regression (SVR), random forest (RF), Gaussian process regression (GP), deep neural networks (DNN), and graph neural networks (GNN), to evaluate their predictive performance for reservoir temperature estimation. Enhanced feature engineering techniques, including accumulated local effects (ALE) and SHAP value analysis, are employed to improve model interpretability and identify key hydrogeochemical predictors. Results demonstrate that RF outperforms other models, achieving the lowest mean squared error (MSE = 66.16) and highest R2 score (0.977), which is attributed to its ensemble learning approach and robust handling of nonlinear relationships. SVR and GP exhibit moderate performance, while DNN and GNN show limitations due to overfitting and sensitivity to hyperparameter tuning. Feature importance analysis reveals that SiO2 concentration as the most influential predictor, aligning with domain knowledge. The study highlights the interplay between model complexity, dataset size, and predictive accuracy, offering actionable insights for optimizing geothermal energy systems. By integrating advanced machine learning with enhanced feature engineering, this research provides a robust framework for improving reservoir temperature prediction, contributing to the sustainable development of geothermal energy in alignment with sustainable energy development.